Foraging habitat of a declining Scottish Red-billed Chough Pyrrhocorax pyrrhocorax population in the post-breeding period. Issue 1 (2nd January 2019) - Gilbert, Gillian; MacGillivray, Fiona S.; McKay, Clive R.; Robertson, Helen S.
ABSTRACT: Capsule: A declining Red-billed Chough Pyrrhocorax pyrrhocorax population, observed during the post-breeding period, used dung and soil-based habitat features as frequent and consistent food sources, but this had not changed from when the population was healthy. Aims: To quantify use of different food sources by Red-billed Choughs in the post-fledging period and to measure any changes since 1989. To find habitat characteristics of soil-based foraging positions, and to highlight food sources that were used more by first-year birds. Methods: In 2013 on Islay, Inner Hebrides, we recorded the foraging habitat of Red-billed Choughs at different spatial scales in the same location and using the same methods as a study in 1989. We made more detailed measures of foraging habitat in 2011–13 across other areas of Islay. Results: At a large scale, dune pasture was the most preferred foraging habitat. There were indications of a change in preference with time in line with availability of seasonal habitats, such as cut silage and barley stubbles, and preference for foraging in fields with greater livestock density. Within preferred habitats, the most used sources of food at a small patch scale were dung and the soil around rocky outcrops; overall, this had not changed when compared between the declining 2013 population and healthy 1989 population. Soil at chough foraging locations was relatively drier and characterized by short, sparse, vegetation and a slight slope. We found that young birds foraged twice as frequently in dung compared to adults, while adults foraged twice as much in soil. Conclusions: During the post-fledging period, consistent, reliable dung and soil-based features provide sources of invertebrate food for choughs, are as important now as they were 24 years before. These are at least equally as important as the opportunity and variety provided by seasonally available sources such as cut silage and barley stubble.